The spectacular staging of art in the age of AI images (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2025)
This research focuses on the status of the spectacular in relation to the rapid development of images generated by AI technologies. To this end, it proposes an analysis of three characteristics of certain contemporary artistic performances: 1) the use of large immersive formats, 2) the pursuit of notoriety and attention, and 3) the application of excessive and repetitive visual forms.
Keywords: Art; spectacle; AI; staging